Sustained effects of bladder point-of-care ultrasound simulation exercise on nursing students: A prospective cohort study - Tomoyoshi Naito; Akiko Hashizumi; Masako Sakai; Emiko Yamamura; Miho Iwase; Kiyomi Yamada; Masako Watanabe; Nobuo Kimura; Takako Kato; Eiko Fujimoto; Rie Kashihara (BMC Medical Education)
Abstract Background Point-of-care ultrasound (POCUS) can be used in a variety of clinical settings and is a safe and powerful tool for ultrasound-trained healthcare providers, such as physicians and nurses; however, the effectiveness of ultrasound education for nursing students remains unclear. This prospective cohort study aimed to examine the sustained educational impact of bladder ultrasound simulation among nursing students. Methods To determine whether bladder POCUS simulation exercises sustainably improve the clinical proficiency regarding ultrasound examinations among nursing students, evaluations were conducted before and after the exercise and were compared with those after the 1-month follow-up exercise. A bladder urine volume measurement simulator and a portable ultrasound device were used during the exercise. Nursing student volunteers participated in this prospective observational study. The primary outcome was the Objective Structured Assessment of Ultrasound Skills (OSAUS) score. The secondary outcomes were the Self-Directed Learning Readiness Scale (SDLRS) and Student Satisfaction and Self-Confidence in Learning (SSSCLS) scores. Differences were analyzed using one-way analysis of variance with repeated measures. Results Data from 12 students were analyzed. The percentages of total OSAUS scores increased from 34.3% after the initial bladder POCUS simulation exercise to 51.0% after the 1-month follow-up exercise (p < 0.001). The OSAUS scores for several subdomains, including image optimization, systematic reviews, image interpretation, test documentation, and medical decision-making, increased significantly. In addition, the SDLRS significantly increased from 204.4 before the exercise to 233.6 after the 1-month follow-up exercise (p < 0.001), and the SSSCLS confidence scores also increased from 33.7 after the initial exercise to 36.4 after the 1-month follow-up exercise (p < 0.005). Conclusion The bladder POCUS simulation exercise is effective in continuously improving the clinical performance of nursing students for ultrasound examinations even at 1-month follow-up, increasing their confidence and promoting a self-directed learning attitude.